Impact of Vitamin D repletion on treatment of chronic lower back pain - Khan, Dildar; Muhammad Muneeb; Khan, Hameed Ullah; Rajput, Aatir H; Ali, Abid; Memon, Zaheer Hussian (International Journal of Endorsing Health Science Research, 2019)
Background: Chronic lower back pain is precisely a distressing condition not only because of associated physical debilitation but the psychological hassle as well. Along with various etiological factors, low vitamin D levels in the body is also a significant cause of this ailment. This study focuses on monitoring the effect of Vitamin D repletion on intensity of chronic (non-traumatic) lower back pain. Methodology: This longitudinal-prospective analysis was conducted upon a sample of 374 lower back pain patients presenting with vitamin D deficiency from February to October 2018. Inquiries were made regarding basic socio-demographics, history of chronic lower back pain, dietary and medicinal supplement usage, hours of sun exposure and pain levels, assessed using a Visual Analogue Scale (VAS). The vitamin D levels and the VAS pain score were assessed upon baseline visit to the orthopedic out-patient department and followed up after 2 months (1st follow up visit) and 6 months (2nd follow up visit). Data obtained was analyzed using SPSS version 21.0 and Microsoft Excel 2013. Results: Among the 374 respondents, 52.67% were males while 47.33% were females with the mean age of 47.5 years. The mean baseline (pre-intervention) vitamin D levels were found to be 10.3 ng/ml, which raised significantly to 34.3 ng/ml. The mean (pre-intervention) VAS score dropped significantly, from 81.9 at baseline visit to 31.4 at 2nd follow up visit. Conclusion: It is concluded that vitamin D repletion has a marked impact on reducing the intensity of chronic lower back pain. Future studies may confirm further to validate the findings of this research.